An Analysis on Readability of English Reading Texts With Automated Computer Tool - Yulianto Yulianto (UIR Press, 2019)
Selecting appropriate textbook to the students is important because textbook have dominant role in the success of foreign language teaching and learning. The purpose this article is to analyze the readability level of English reading texts with automated computer tools. There are eight reading texts that will be analyzed in this qualitative study. The data and source of data of this research were adopted from an English textbook entitled Pathway to English 2 Textbook for the Eighth Grade of Junior High School Students Published by Erlangga. The results reveal that only 1 text was appropriate for seven or eight grade of Junior High School students. There were 6 texts appropriate elementary students. And there was 1 text suitable for Senior High School students.